9 is added to both sides of the equation then you would combine like terms
Answer:
0, - 6, - 12
Step-by-step explanation:
To find the first 3 terms, substitute n = 1, 2, 3 into the formula
a₁ = 3(- 2)(1 - 1) = 3 × - 2 × 0 = 0
a₂ = 3(- 2)(2 - 1) = 3 × - 2 × 1 = - 6
a₃ = 3(- 2)(3 - 1) = 3 × - 2 × 2 = - 12
First 3 terms are 0, - 6, - 12
What is that other number to the right of the red and I can answer it
Answer:
18x^2+6
Step-by-step explanation:
2(9x^2+3)
multiply each term in parentheses by 2
2 x 9x^2+2 x 3
calculate product
18x^2+2 x 3
multiply numbers
18x^2+6
Answer it is 65
Step-by-step explanation: